Anthologie de la prose neo-Hellenique (1884-1948) - Mirambel, Andre (Librairie C. Klincksieck, 1950)
Ροΐδης -- Βιζυηνός -- Παπαδιαμάντης -- Κονδυλάρης -- Ψυχάρης -- Καζαντζάκης -- Ξενόπουλος -- Μυριβήλης -- Κόντογλου -- Βενέζης -- Θεοτοκάς -- Τερζάκης κ.αλ.